Type III procollagen peptide level can indicate liver dysfunction associated with volume overload in acute heart failure. (14th March 2022) - Shirakabe, Akihiro; Okazaki, Hirotake; Matsushita, Masato; Shibata, Yusaku; Shigihara, Shota; Nishigoori, Suguru; Sawatani, Tomofumi; Sasamoto, Nozomi; Kiuchi, Kazutaka; Atsukawa, Masanori; Itokawa, Norio; Arai, Taeang; et al.
Abstract: Aim: The role of serum type III procollagen peptide (P3P) level in the acute phase of acute heart failure (AHF) requires clarification. We hypothesized that serum P3P level is temporarily higher during the acute phase, reflecting liver dysfunction due to congestion. Methods and results: A total of 800 AHF patients were screened, and data from 643 patients were analysed. Heart failure was diagnosed by the treating physician according to the European Society of Cardiology (ESC) guidelines, and included patients being treated with high‐concentration oxygen inhalation (including mechanical support) for orthopnea, inotrope administration, or mechanical support for low blood pressure, and various types of diuretics for peripheral or pulmonary oedema. In all cases, diuretics or vasodilators were administered to treat AHF. The patients were divided into three groups according to their quartile (Q) serum P3P level: low‐P3P (Q1, P3P ≤ 0.6 U/mL), mid‐P3P (Q2/Q3, 0.6 < P3P <1.2 U/mL), and high‐P3P (Q4, P3P ≥ 1.2 U/mL). The plasma volume status (PVS) was calculated using the following formula: ([actual PV − ideal PV]/ideal PV) × 100 (%). The primary endpoint was 365 day mortality. A Kaplan–Meier curve analysis showed that prognoses, including all‐cause mortality and heart failure events within 365 days, were significantly ( P < 0.001) worse in the high‐P3P group when compared with the mid‐P3P and low‐P3P groups. A multivariate logistic regression analysis showed that high PVS (Q4, odds ratio [OR]: 4.702, 95% CI: 2.012–20.989, P < 0.001), high fibrosis‐4 index (Q4, OR: 2.627, 95% CI: 1.311–5.261, P = 0.006), and low estimated glomerular filtration rate per 10 mL/min/1.73 m 2 decrease (OR: 1.996, 95% CI: 1.718–2.326, P < 0.001) were associated with high P3P values. The Kaplan–Meier curve analysis demonstrated a significantly lower survival rate, as well as a higher rate of heart failure events, in the high‐P3P and high‐PVS groups when compared with the other groups. A multivariate Cox regression model identified high P3P level and high PVS as an independent predictor of 365 day all‐cause mortality (hazard ratio [HR]: 2.249; 95% CI: 1.081–3.356; P = 0.026) and heart failure events (HR: 1.586, 95% CI: 1.005–2.503, P = 0.048). Conclusion: A high P3P level during the acute phase of AHF served as a comprehensive biomarker of liver dysfunction with volume overload (i.e. liver congestion) and renal dysfunction. A high P3P level at admission may be able to predict adverse outcomes in AHF patients.